Dampak Kebakaran Hutan Terhadap Tutupan Lahan, Komposisi dan Struktur Serta Keanekaragaman Vegetasi di Taman Nasional Manupeu Tanah Daru dan Laiwangi Wanggameti (TN Matalawa) (Studi Kasus Blok Hutan Kambata Wundut, Desa Kambata Wundut, Kecamatan Lewa - Sesilia Bria Seran; Ludji Michael Riwu Kaho; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Various environmental issues faced by the world in general and Indonesia in particular are highly diverse, one of which is forest and land fires (karhutla). A fire incident refers to a condition where fire burns a specific area or region, while a forest is an extensive land area dominated by trees. Thus, in general, forest fires refer to the burning of a vast area filled with trees and other vegetation. Forest and land fires occur regularly every year in the Matalawa National Park area. This study aims to determine whether there are differences in composition, structure, and vegetation diversity between burned and unburned areas in the Kambata Wundut Forest Block, Kambata Wundut Village. This research employs a spatial analysis approach using the Google Earth Engine platform and vegetation analysisThe results show that forest and land fires can influence the composition of stand-forming vegetation. There are differences in composition and structure between burned and unburned areas, where some vegetation types are found only in one area, while most dominant vegetation species are present in both. The vegetation diversity index at all growth phases is generally in the high category, while the species richness index tends to be low. Additionally, the species evenness index indicates high values across all growth phases. The comparison of vegetation species similarity levels between the two areas shows a very high percentage, indicating that the vegetation growing in both burned and unburned areas is relatively similar. However, vegetation diversity in the unburned area is higher than in the burned area.